Size and Shape Design Optimization of Truss Structures Using the Jaya Algorithm - Grzywiński, Maksym (Computer Assisted Methods in Engineering and Science; Vol 27 No 2-3 (2020), 2020)
The metaheuristic algorithm is proposed to solve the weight minimization problem of truss structures, considering the shape and sizing design variables. Design variables are discrete and/or continuous. The design of truss structures is optimized by an efficient optimization algorithm called Jaya. The main feature of Jaya is that it does not require setting algorithm-specific parameters. The algorithm has a very simple formulation in which the basic idea is to approach the best solution and escape from the worst solution [6]. Analyses of structures are performed by a finite element code in MATLAB. The effectiveness of the Jaya algorithm is demonstrated using two benchmark examples: planar truss 18-bar and spatial truss 39-bar, and compared with results in references.